THE IMPLEMENTATION OF SEARCH ENGINE OPTIMIZATION TO IMPROVE CONSUMER BUYING INTEREST CASE IN MICRO, SMALL, AND MEDIUM ENTERPRISES - Suranto, Suranto; Faradillah Aisha Maharani; Mila Faila Sufa; Etika Muslimah; Afiqoh Akmalia Fahmi; Farid Adi Prasetya (SEAN Institute, 2023)
This study explores the impact of Search Engine Optimization (SEO) implementation, spanning TikTok, Facebook, Instagram, and website utilization, on consumer buying interest within the context of Haji Edi's hotplate chicken noodle micro, small, and medium enterprises (MSMEs) in Surakarta, Indonesia. Rooted in contemporary marketing strategies, it underscores the significance of segmentation, targeting, and positioning (STP) to nurture customer loyalty and fuel business growth. The findings reveal that SEO, with a specific emphasis on Instagram, exerts a substantial influence on consumer buying interest, resulting in heightened sales. Notably, product quality, particularly the delectable taste of chicken noodles and meatballs, emerges as a pivotal driver of consumer buying interest, further amplifying the efficacy of the marketing strategy. This research adds a valuable perspective to the literature by showcasing the untapped potential of SEO, especially on social media platforms, in propelling consumer buying interest traditional MSMEs in the Indonesian market.